2017
DOI: 10.1063/1.5014012
|View full text |Cite
|
Sign up to set email alerts
|

Using mathematical software to design power electronic converters

Abstract: Abstract. In the paper is presented mathematical software, which was used for design of power electronic devices. Examined to different example, which are applied to designing electronic converters. In this way, it is possible to play different combinations of the circuit elements by simple means, thus optimizing according to certain criteria and limitations. Free software with a simple and intuitive interface is selected. No special user training is required to work with it and no further training is required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…This is because they are familiar with the use of mathematical programs, as the latter is an integral part of their course curriculum. The ease of use of mathematical programs in designing and analysis of electronic circuits has also been experienced earlier by many researchers [10]- [12], [29]. When asked about the flexibility provided by the simulation tools, a majority of respondents answered in favor of using programming tools in comparison to doing the designing and analysis manually in the labs, as these tools comfortably provide a route that allows for cycling different scenarios of the circuit design [10], [11].…”
Section: A Survey Report and Analysismentioning
confidence: 94%
See 4 more Smart Citations
“…This is because they are familiar with the use of mathematical programs, as the latter is an integral part of their course curriculum. The ease of use of mathematical programs in designing and analysis of electronic circuits has also been experienced earlier by many researchers [10]- [12], [29]. When asked about the flexibility provided by the simulation tools, a majority of respondents answered in favor of using programming tools in comparison to doing the designing and analysis manually in the labs, as these tools comfortably provide a route that allows for cycling different scenarios of the circuit design [10], [11].…”
Section: A Survey Report and Analysismentioning
confidence: 94%
“…The usage of mathematical software to design and analyze various electronic circuits has been explored earlier and found to be an important tool as it provides many benefits that traditional way of cook book method cannot provide [10]- [12], [29]. Wanhammar has shown that electronic op-amp based circuits at undergraduate level could be beautifully realized with the help of mathematical programs written in MATLAB [29].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations